PENGARUH MODEL COOPERATIVE LEARNING TIPE TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PERMAINAN ULAR TANGGA TERHADAP HASIL BELAJAR KOGNITIF IPAS SISWA KELAS IV SD - Muslimah Apriliya; Nurdiansyah, Nurdiansyah; Jennyta Caturiasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effect of the cooperative learning model of Team Games Tournament (TGT) assisted by the snake and ladder educational game on fourth-grade elementary students’ cognitive learning outcomes in the IPAS subject. It also compares the effectiveness of the TGT model with the STAD type of cooperative learning. The research employed a quasi-experimental method using a nonequivalent control group design. The sample consisted of class IVA as the control group and class IVB as the experimental group, selected randomly using a spinning method. Data were collected through pretest and posttest assessments. Statistical analysis was conducted using SPSS version 23. The results of a simple linear regression test revealed an R-square value of 0.519, indicating that the TGT model assisted by the snake and ladder game contributed 51.9% to students’ cognitive learning outcomes. The average n-gain score of the experimental group was 0.6137, while the control group scored 0.3859. Although both scores fall into the medium improvement category, the experimental group showed higher gains. Therefore, it can be concluded that the use of the TGT model supported by the snake and ladder media is more effective than the STAD model in enhancing fourth-grade students' cognitive learning outcomes in the IPAS subject.